The Audible Memory Shocks in Abbasid Poetry that Lament Imam Al-Hussein by choic - wisam muhammad aboud, Assist. Lect. (lark, 2021)
There is no doubt that a lot of the shocking tales and discouraging facts we hear remain stuck in our minds and we regurgitate them from time to time. They add a touch of sadness to what we remember of our lives since we recall the main events in our imaginations and experience feelings, some of which we may not be able to describe, that somewhat match what we experienced when we first heard the news or stories that shocked us. To sum up, let us say that the incident of Al-Tuff has occupied the hearts of Shiite poets and lovers in different eras due to the horror that befell the family of the Messenger of God, that is, killing, captivity, and infringement on the rights of the son of a prophet’s daughter. The lives of his companions and brothers were taken before his eyes.